PEMBERDAYAAN DIVISI KEPUTRIAN REMAJA MASJID ALMASYHUDA BEKASI DALAM MENINGKATKAN PENGETAHUAN REMAJA MENGENAI MANAJEMEN MENSTRUASI - Nina Primasari; Fauziah Yulfitria; Yudhia Fratidhina (IFI cabang Kota Bekasi, 2022)
Menstruation is the discharge of blood from the vagina due to the shedding of the endometrial wall. Menstruation occurs every month in women of childbearing age and is a natural process. Although menstruation is a natural process, there are still many teenagers who consider menstruation to be a sensitive and taboo subject to talk about, so they are more introverted and embarrassed to tell it to other people, including their mothers. This makes young women less understand about menstruation. Information about menstruation should be disseminated as early as possible so that adolescents have good mental readiness in dealing with their menarche period and can perform good self-care during menstruation. The purpose of this community service activity is to assist young women in improving their health status through increasing knowledge, attitudes and behavior about menstrual management and being able to disseminate menstrual management information to their peers. Methods of implementing community service activities identify problems, potential partners and involve young women directly in every activity by using booklets and video media. The results of community service activities include an increase in the knowledge of young women about menstruation, the formation of a group of teenagers who care about reproductive health and the implementation of counseling activities on menstrual management to peers by the youth division of the Al Masyhuda mosque in Bekasi. It is expected that young women can apply the knowledge received in everyday life and can provide counseling and counseling to their peers as a source of educational information about menstrual management.